Characterization of Trypsin-Like Protease of Lactobacillus plantarum FNCC 0270 - Trismilah Margono; Wahono Sumaryono; Amarila Malik; Mohamad Sadikin (Bogor Agricultural University, Indonesia, 2014)
Trypsin is an enzyme that has a unique mechanism of cutting peptide bonds specifically at the carboxyl side of lysine or arginine amino acids, with another amino acid. This study aims to analyze a trypsin-like protease (TLP) found in Lactobacillus plantarum FNCC 0270, by performing partial proteomic tests, i.e. MALDI-TOF/TOF, and standard bioinformatics tools. SDS-PAGE analysis showed 4 protein bands. Two bands of the (P1 and P2) showed molecular weights equivalent to 47.35 and 38.42 kD, each generating 8 and 11 peptide fragments respectively. According to information in www.ncbi.nlm.nih.gov/genbank/structures, the structure of serine protease HtrA (subs. plantarum L. plantarum ST–III) consists of three domains. Using Clone Manager® software by aligning two sequences we obtained eleven. The Lactobacillus produces of the trypsin-like serine protease has 40-90% similarity. Using the Clustal W2 software we passed the 11 sequences through multiple alignments, and found that the isolate L. plantarum is closely related to L. buchneri, L. brevis, and L. malefermentans on the phylogenetic tree. Alignment analysis results showed that all 8 peptide fragments of band 1 and 11 peptide fragments of band 2, of the SDS-PAGE, were located in the active domain region of the fourth trypsin-like serine protease producing Lactobacilli.